The Transition to Self-Employment and Perceived Skill-Mismatches: Panel Data Evidence from Eleven EU Countries - Judit Albiol Sanchez; Luis Diaz-Serrano; Mercedes Teruel (Institute of Labor Economics (IZA), 2020)
Some studies using either objective or subjective indicators, find that self-employed individuals are less likely to be or to report being skill-mismatched in comparison with salaried employees. The aim of this paper is to analyze the impact of the transition from salaried employment to self-employment on self-reported skill mismatches. To do so, this article uses eight waves of the European Community Household Panel covering the period 1994–2001. The panel data nature of this rich dataset, allows us to track individuals over time and measure self-reported skill-mismatches before and after the transition for the same individuals, using as the comparison group those individu-als who remain in salaried employment during the whole sample period. Our empirical findings indicate that those individuals who transit from salaried employment to self-employment reduce their probability to report being skill-mismatched after the transition. Interestingly, we also observe that this effect vanish if the transition is done from an unemployment status, and that the effect is quite heterogenous across countries.
Keywords: L26; J24; B23; 330; self-employment; skill mismatches; salaried employment; job transitions